2017
DOI: 10.1016/j.stemcr.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Inflammation-Responsive Astrocytes from Glial Progenitors Generated from Human Induced Pluripotent Stem Cells

Abstract: SummaryAstrocyte dysfunction and neuroinflammation are detrimental features in multiple pathologies of the CNS. Therefore, the development of methods that produce functional human astrocytes represents an advance in the study of neurological diseases. Here we report an efficient method for inflammation-responsive astrocyte generation from induced pluripotent stem cells (iPSCs) and embryonic stem cells. This protocol uses an intermediate glial progenitor stage and generates functional astrocytes that show level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
146
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(162 citation statements)
references
References 57 publications
15
146
1
Order By: Relevance
“…iPSCs as disease models iPSCs were initially used to model diseases with highly penetrant genetic variants (Box 1) of large phenotypic effect (Cao et al, 2016;Liu et al, 2011;Wainger et al, 2014), but more recently they have been used to study common genetic variants of modest effect size that drive complex diseases. They provide a key platform to study the impact of human cell type-specific gene regulation, as they can recapitulate the broad regulatory profile of their in vivo counterparts and also mirror tissue-specific functional genetic variation (Banovich et al, 2018;Santos et al, 2017). Moreover, large-scale iPSC-based studies have identified expression quantitative traitassociated loci (eQTLs; Box 1) that inform on the interpretation of variants identified by genome-wide association studies (GWAS; Box 1) (Carcamo-Orive et al, 2017), as well as protein quantitative trait loci that give insights into mechanisms through which diseaseassociated genetic risk modulates cell physiology (Mirauta et al, 2018 preprint).…”
Section: Introductionmentioning
confidence: 99%
“…iPSCs as disease models iPSCs were initially used to model diseases with highly penetrant genetic variants (Box 1) of large phenotypic effect (Cao et al, 2016;Liu et al, 2011;Wainger et al, 2014), but more recently they have been used to study common genetic variants of modest effect size that drive complex diseases. They provide a key platform to study the impact of human cell type-specific gene regulation, as they can recapitulate the broad regulatory profile of their in vivo counterparts and also mirror tissue-specific functional genetic variation (Banovich et al, 2018;Santos et al, 2017). Moreover, large-scale iPSC-based studies have identified expression quantitative traitassociated loci (eQTLs; Box 1) that inform on the interpretation of variants identified by genome-wide association studies (GWAS; Box 1) (Carcamo-Orive et al, 2017), as well as protein quantitative trait loci that give insights into mechanisms through which diseaseassociated genetic risk modulates cell physiology (Mirauta et al, 2018 preprint).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of human embryonic stem cell and induced pluripotent stem cell (iPSC) technology has enabled large-scale generation of human astrocytes and other CNS cells that retain the genetic information of the patient, as powerful human in vitro models of disease (reviewed in 14 ) . Several protocols to generate astrocytes have been developed by independent groups, using either a specific gradient of patterning agents to mimic embryonic development [15][16][17][18][19][20][21] or overexpression of critical transcription factors 22,23 . Usually, iPSC differentiation into astrocytes in monolayer cultures does not require a purification step; in recent years, however, more complex 3D cultures of CNS organoids have been established that contain neural progenitor cells, neurons, oligodendrocyte lineage cells and microglia, in addition to astrocytes 22,[24][25][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…Gene programs induced when astrocytes enter a reactive state are similar to those of the MES GBM subtype To examine connections between the MES GBM transcriptome profile and the astrocytic response during neuroinflammation, we set up an in vitro model to study the transition of astrocytes into a reactive cell state. In brief, cultured human primary astrocytes were exposed to TNFα or IL1β, which resulted in NFκB activation ( Figure 1A) and upregulation of genes coupled to proinflammatory response, CSF1, CCL2, and MX1 [20][21][22][23] ( Figure 1B). Next, we analyzed changes in the whole transcriptome during long-term treatment with IL1β (12 days).…”
Section: Resultsmentioning
confidence: 99%